Green-Synthesized Silver Nanoparticle-Loaded Antimicrobial Films: Preparation, Characterization, and Food Preservation - Wenxi Yu; Qin Lei; Jingxian Jiang; Jianwei Yan; Xijian Yi; Juan Cheng; Siyu Ou; Wenjia Yin; Ziyan Li; Yuru Liao (Foods, 2025)
This study presented a novel antimicrobial packaging PVA/xanthan gum film decorated with green-synthesized silver nanoparticles (AgNPs) derived from Myrica rubra leaf extract (MRLE) for the first time. Montmorillonite (MMT) was used to improve its dispersion (AgNPs@MMT). The synthesis time, temperature, and concentration of AgNO3 were considered using a central composite design coupled with response surface methodology to obtain the optimum AgNPs (2 h, 75 °C, 2 mM). Analysis of substance concentration changes confirmed that the higher phenolic and flavonoid content in MRLE acted as reducing agents and stabilizers in AgNP synthesis, participating in the reaction rather than adsorbing to nanoparticles. TEM, XRD, and FTIR images revealed a spherical shape of the prepared AgNPs, with an average diameter of 8.23 ± 4.27 nm. The incorporation of AgNPs@MMT significantly enhanced the mechanical properties of the films, with the elongation at break and shear strength increasing by 65.19% and 52.10%, respectively, for the PAM2 sample. The films exhibited strong antimicrobial activity against both Escherichia coli (18.56 mm) and Staphylococcus aureus (20.73 mm). The films demonstrated effective food preservation capabilities, significantly reducing weight loss and extending the shelf life of packaged grapes and bananas. Molecular dynamics simulations reveal the diffusion behavior of AgNPs in different matrices, while the measured silver migration (0.25 ± 0.03 mg/kg) complied with EFSA regulations (10 mg/kg), confirming its food safety. These results demonstrate the film’s potential as an active packaging material for fruit preservation.